Concentrations of endocrine disrupting chemicals in newborn blood spots and infant outcomes in the upstate KIDS study. (December 2018) - Bell, Erin M.; Yeung, Edwina H.; Ma, Wanli; Kannan, Kurunthachalam; Sundaram, Rajeshwari; Smarr, Melissa M.; Buck Louis, Germaine M.
Abstract: Background: Novel methodologies to quantify infant exposures to endocrine disrupting chemicals (EDCs) for population-based studies are needed. Objectives: We used newborn dried blood spots to quantify three EDCs and their associations with infant outcomes in the Upstate KIDS Cohort. Methods: We measured bisphenol A (BPA), perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in 2071 singleton and 1040 twin infants born to mothers in New York State. We log transformed concentrations after rescaling by their standard deviations and modeled each in relation to gestational age, birthweight, length, head circumference and Ponderal Index (PI) using linear regression techniques. All models were adjusted for maternal age, body mass index, education, infertility treatment and parity. Generalized estimating equations with robust standard errors were used to assess the associations for twins. Results: Chemicals were largely quantified above the limits of detection (>99% for PFOS and PFOA; 90% for BPA). Overall, we observed no significant associations between PFASs and birth size irrespective of plurality of birth. However, among twins, BPA was associated with decreases in gestational age (adjusted β = −0.09 weeks; 95% Confidence Interval (CI): −0.16, −0.02) and birthweight (adjusted β = −32.52 g; 95% CI: −60.99, −4.05), head circumference (adjusted β = −0.18 cm; 95% CI: −0.38, −0.02) and increased PI in singletons (adjusted β = 0.02 cm; 95% CI: 0.004, 0.04). Conclusion: We observed negative associations between BPA and birth size in twins. Our findings demonstrate the feasibility of newborn dried blood spots for quantifying neonatal exposure at the population level. Highlights: Used newborn dried blood spots to quantify BPA, PFOS and PFOA Observed inverse association between BPA and birth size in twins No observed association between BPA and birth size in singletons No observed association with PFOS and PFOA and birth size, regardless of plurality